Pakistan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper and Statistical Appendix on Pakistan looks at the worrisome trend of declining growth from a growth-accounting point of view. The paper provides considerable evidence that Pakistan's striking 'social gap' in education and health is indeed a main culprit for a weakening growth performance. It looks at the financial sector as an additional area that is central for growth and governance, and where reforms are well advanced. The paper also analyzes how to ensure a continuation of prudent fiscal policies in Pakistan that would reduce public debt to more sustainable levels.